Inclusiveness of BUMDes Services through Service Quality Based on the SERVQUAL Model : Case Study in Daha Utara District - Rusdi Rusdi; Ika Devi Pramudiana; Ferry Ramadhan; Sri Kamariyah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Inclusive village development is a strategic priority in realizing the Sustainable Development Goals (SDGs), with Village-Owned Enterprises ( BUMDes ) as the driving force of the local economy. However, the participation of vulnerable groups—such as people with disabilities , the elderly, women, and the poor—is still limited in BUMDes services . This study aims to evaluate the quality of BUMDes services in Daha Utara District through the SERVQUAL (Service Quality) approach which includes five dimensions: tangibles , reliability , responsiveness , assurance , and empathy . The research method used is descriptive qualitative with a phenomenological approach . Data were collected through semi-structured interviews with three categories of participants: BUMDes managers , vulnerable groups, and community leaders. The results of the study indicate that physical facilities ( tangibles ) are not inclusive, service reliability is disrupted by limited human resources, and the assurance dimension has not been supported by ongoing training. Meanwhile, the responsiveness and empathy dimensions are relatively good interpersonally , but are not yet structured institutionally. The main obstacles identified are the lack of budget, lack of training, and the absence of a formal complaint mechanism. On the other hand, moral support from village managers and figures is a supporting factor for service transformation. This study concludes that improving the quality of inclusive services requires a transformative and participatory approach , including adaptive digitalization and active involvement of vulnerable groups in planning. These findings are expected to be the basis for making fairer and more responsive village development policies.